Diffusion Tensor Imaging Tractography of White Matter Tracts in the Equine Brain - Boucher, Samuel; Arribarat, Germain; Cartiaux, Benjamin; Lallemand, Elodie Anne; Péran, Patrice; Deviers, Alexandra; Mogicato, Giovanni (Frontiers in Veterinary Science, 2020)
Tractography, a non-invasive technique tracing brain pathways from Diffusion Tensor magnetic resonance Imaging (DTI) data, is increasingly being used for brain investigation of domestic mammals. In the equine species, such a technique could be useful to improve our knowledge about structural connectivity or to assess structural changes of white matter tracts potentially associated with neurodegenerative diseases. The goal of the present study was to establish the feasibility of DTI tractography in the equine brain and provide a morphologic description of the most representative tracts in this species. Post mortem DTI and susceptibility-weighted imaging (SWI) of an equine brain were acquired with a 3 Tesla system using a head coil. Association, commissural and projection fibers, the three fiber groups typically investigated in tractography studies, were successfully reconstructed and overlaid on SWI or fractional anisotropy maps. The fibers derived from DTI correlate well with their description in anatomical textbooks. Our results demonstrate the feasibility of using post mortem DTI data to reconstruct the main white matter tracts of the equine brain. Further DTI acquisitions and corresponding dissections of equine brains will be necessary to validate these findings and create an equine stereotaxic white matter atlas that could be used in future neuroimaging research.